Counseling of Automation-Based Hydroponic Planting System in Ciparay Village - Lucia Jambola; Dini Fauziah; Ratna Susana; Niken Syafitri; Lita Lidyawati (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
The people in Ciparay Village faced economic problems due to layoffs by companies during the pandemic, so they had to change professions, one of which was to become a farmer. In 2014, the Ciparay Village’s Woman Farmer Group developed a hydroponic system but it was failed due to lack of knowledge. This PKM activity aimed at: 1) increasing partners’ knowledge on good and effective farming methods, 2) increasing partners’ knowledge on how to manufacture and work an automation-based hydroponic system, as additional knowledge for the people in Ciparay Village. By achieving these goals, it is hoped that the Ciparay Village community are able to develop the system of which results can become their own food source or be sold as their main or additional income. The method used in this activity was the approach and participation of partners, in which the team with the partners were directly involved proactively, and used solution-based approach in the form of training, mentoring and automation-based hydroponic system simulation as a solution to the main problems of partners.